An Evaluation of Non-Performing Assets of Indian Banking Sector - A Case study - Dr. Rajappa L; Dr. Sarala M S (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The amount of NPAs indicates best about the strength of banking sector in a country. In India NPAs are showing an upward trend due to lack of governance and weakness in credit administration. State owned banks control 70% of banking industry by assets but carries over 90% of total bad loans. According to RBI the gross NPAs in Indian banks specifically in public sector banks are valued around Rs. 400000 crores (Approximately USD 61.5 Trillions) which represents 90% of the total NPA in India and the rest private sector (CFI, NPAs in Indian banks finance institute.com). The presence of high level of NPAs suggests about innumerable credit defaults which affects the profitability and net worth of assets of banks. Therefore NPAs should not be allowed to reach a problematic stage. High level of NPAs degrade a banks credit rating, lowering its creditability and capacity to raise additional capital (Suresh Kumar, 2014). An attempt is made in this research paper to showcase the level of NPAs management in public sector, private sector and SBI associates. Further, the recent developments to tackle NPSs is also presented.